2007
DOI: 10.1038/sj.sc.3102100
|View full text |Cite
|
Sign up to set email alerts
|

Postural responses during falling with rapid reach-and-grasp balance reaction in patients with motor complete paraplegia

Abstract: Study design: Cross-sectional study. Objectives: To investigate the kinematic, kinetic and electromyographic (EMG) aspects of postural control during falling with rapid reach-and-grasp balance reaction in thoracic cord-injured individuals wearing knee-ankle-foot orthoses (KAFOs). Setting: Institutional Motion Analysis Laboratory. Methods: Seven T7-T12 cord-injured subjects with complete motor loss (ASIA classes A and B) participated in this study. Subjects with KAFOs first stood steady with a modified walker a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…With the development of theoretical and experimental methods to improve accuracy and reliability, human motion analysis has become a useful investigative and diagnostic tool in many research and clinical areas, such as medicine, ergonomics and sports, to name but a few. Through human motion analysis, the deviations from normal movement in terms of the altered kinematic, kinetic or EMG patterns can be identified and then used to evaluate the neuromusculoskeletal conditions, to help with subsequent treatment planning and/or to assess the efficacy of treatment in various patient groups, such as those with CP [18,19], stroke [55–61], knee osteoarthritis (OA) [62–69], diabetes mellitus (DM) [70,71], and spinal cord injury (SCI) [72]. Human motion analysis has also seen many applications in assistive technology, such as prosthetics and orthotics, in which accurate evaluation of critical joint motion characteristics can be obtained from human motion measurements.…”
Section: Applications Of Human Motion Analysismentioning
confidence: 99%
“…With the development of theoretical and experimental methods to improve accuracy and reliability, human motion analysis has become a useful investigative and diagnostic tool in many research and clinical areas, such as medicine, ergonomics and sports, to name but a few. Through human motion analysis, the deviations from normal movement in terms of the altered kinematic, kinetic or EMG patterns can be identified and then used to evaluate the neuromusculoskeletal conditions, to help with subsequent treatment planning and/or to assess the efficacy of treatment in various patient groups, such as those with CP [18,19], stroke [55–61], knee osteoarthritis (OA) [62–69], diabetes mellitus (DM) [70,71], and spinal cord injury (SCI) [72]. Human motion analysis has also seen many applications in assistive technology, such as prosthetics and orthotics, in which accurate evaluation of critical joint motion characteristics can be obtained from human motion measurements.…”
Section: Applications Of Human Motion Analysismentioning
confidence: 99%
“…Studies have assessed FOF in the elderly population [9] and in persons with Parkinson disease [10] and stroke [11]. Lin et al investigated the kinematic, kinetic, and electromyographic aspects of postural control during falling with rapid reach-and-grasp balance reaction in individuals with thoracic (T) SCI wearing KAFOs [12]. They concluded that back postural muscles alone are not sufficient to maintain balance.…”
Section: Introductionmentioning
confidence: 99%
“…6,14 Brotherton et al, 6 stated that postural control has an essential role in the prevention of falls, as patients with good postural control demonstrate better walking and standing performance. Lin et al 15 evaluated the kinematics, kinetics and electromyography associated with postural control during static stance when people with SCI voluntarily let go of their walking frame. The resulting instability caused a rapid reach-and-grasp balance reaction in these individuals with thoracic level of injury.…”
Section: Introductionmentioning
confidence: 99%